Analisis Sentimen Ulasan Pengguna Aplikasi Ajaib Menggunakan Metode Naïve Bayes - Hilmy Zhafran Muflih; Allif Rizki Abdillah; Firman Noor Hasan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Developments occurring in the investment sector have made people interested in starting to invest. Currently, investments can be made easily using applications on smartphones, such as the Ajaib application. The Ajaib application offers comfort in making investments with the features, security and convenience provided to users, so that various reviews emerge from users in the form of negative or positive sentiments after using the Ajaib application. From the various reviews given, there are still some people who are still hesitant to use the Ajaib application because of the reviews given by people who have used it. The reviews given by users encouraged researchers to conduct research regarding user views after using the Ajaib application with the Naïve Bayes algorithm. The research was carried out to determine the number of negative and positive sentiments from existing reviews regarding the Ajaib application. Researchers collected 500 data through a scraping process on Google Playstore in the Ajaib application. The results obtained in research on sentiment analysis using the Naïve Bayes algorithm method were 44.2% or 221 positive sentiments and 55.8% or 279 negative sentiments from the 500 sentiment data that had been analyzed. The evaluation process was carried out using a confusion matrix to evaluate the Naïve Bayes algorithm method. The results of the evaluation process obtained an accuracy value of 74.44%.